To evaluate the efficacy of magnesium sulfate and fentanyl as an adjuvant to ropivacaine in supraclavicular brachial plexus block for post-operative pain relief in the upper limb surgeries: A comparative randomized study - Irfan Khan; Neelima Tandon; Manmohan Jindal; Kushal Jethani (Asian Journal of Medical Sciences, 2023)
Background: Adjuvants to local anesthetics have been used to prolong the duration of analgesia after brachial plexus block surgery. This study evaluates the effects of adding magnesium sulfate and fentanyl with ropivacaine in the supraclavicular brachial plexus block to prolong the duration of analgesia. Aims and Objectives: The aim of the present study was to compare the onset and duration of sensory and motor blockade with the quality of perioperative analgesia and post-operative side effects if any, provided by magnesium sulfate and fentanyl as adjuvants to ropivacaine in supraclavicular block. Materials and Methods: A total of 80 patients with American Society of Anesthesiologists Grade I/II scheduled for elective upper limb surgeries were randomly allocated into two groups. Group M received 30 ml of 0.5% ropivacaine with 250 mg magnesium sulfate and Group F received 30 ml of 0.5% ropivacaine with 50 μg fentanyl for supraclavicular brachial plexus block using PNS guidance. The onset and duration of sensory and motor block, time for the requirement of rescue analgesia, and adverse events during the perioperative period were noted. Results: Onset of sensory block. In group M, the mean onset of sensory blockade was 8.91±1.11 min and in Group F, the mean onset of sensory blockade was 12.12±1.14 min. The mean onset of motor block was 11.57±1.62 min in Group M, and 15.17±1.43 min in Group F. Duration of sensory block is 432.9±38.24 min in Group M and 553.45±39.91 min in Group F, respectively, Duration of motor block in Group M is 392.55±35.22 min and in Group F is 517±44.51 min which was statistically significant. Conclusion: Fentanyl prolonged the duration of sensory and motor block and duration of postoperative analgesia as compared to magnesium sulfate when used as an adjuvant to ropivacaine in supraclavicular brachial plexus block and was not associated with any major adverse events.